Sistem Akuisisi Data Besaran Listrik Gedung Komersial - Tangdililing, Ferdianto; Baralangi, Stefany Yunita (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2015)
Utilization of electrical energy in a building direct impact on carbon emissions. One of them in commercial buildings such as campus, industry and banking. Therefore, it needs building management systems by monitoring electrical quantities. This research aims to build a data acquisition system of electrical quantities in commercial buildings. Real time data acquisition by using the Modbus TCP protocol as a communication media between the RTU and MTU integrated with SCADA. LabView is a software that acts as a software tool to visualize data acquisition. Theresults is the utilization of the electrical energy of the building can be monitored so that its use more efficient.Keywords: commercial building, Modbus TCP, monitoring, LabView, SCADA